2014
DOI: 10.1158/1078-0432.ccr-14-0725
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Mediates Regorafenib-Induced Apoptosis in Hepatocellular Carcinoma

Abstract: Purpose: Here, we aim to investigate the molecular mechanism of regorafenib and verify the potential druggable target for the treatment of hepatocellular carcinoma (HCC).Experimental Design: HCC cell lines (PLC5, HepG2, Hep3B, SK-Hep1, and HA59T) were used to investigate the in vitro effect of regorafenib. Phosphatase activity was analyzed in HCC cells and purified SHP-1 proteins. PLC5-bearing mice were used to test the therapeutic efficiency of 20 and 40 mg/kg/d treatment with regorafenib (n ! 8 mice). The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 15 publications
3
61
2
Order By: Relevance
“…Regorafenib, a novel sorafenib derivative, has been approved by the Food and Drug Administration (FDA) for the treatment of metastatic colorectal cancer and advanced gastrointestinal stromal tumors (18). Our previous studies indicated that sorafenib, as an NF-κB signal inhibitor, inhibits the vorinostatand 12-O-tetradecanoylphorbol-13-acetate-induced expression of angiogenesis-and metastasis-associated proteins through the inhibition of NF-κB activation in HCC cells in vitro and in vivo (13,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regorafenib, a novel sorafenib derivative, has been approved by the Food and Drug Administration (FDA) for the treatment of metastatic colorectal cancer and advanced gastrointestinal stromal tumors (18). Our previous studies indicated that sorafenib, as an NF-κB signal inhibitor, inhibits the vorinostatand 12-O-tetradecanoylphorbol-13-acetate-induced expression of angiogenesis-and metastasis-associated proteins through the inhibition of NF-κB activation in HCC cells in vitro and in vivo (13,19).…”
Section: Discussionmentioning
confidence: 99%
“…Regorafenib has been approved for the treatment of metastatic colorectal cancer and advanced gastrointestinal stromal tumors. A randomized double-blinded phase III study of regorafenib in patients with HCC who have progressed after sorafenib treatment is ongoing (18). In our previous studies, sorafenib was revealed to be an inhibitor of NF-κB signaling and reduced NF-κB-modulated expression of proteins including MMP-9 and VEGF in HCC in vitro and in vivo (13,19).…”
Section: Introductionmentioning
confidence: 99%
“…26 Further, a STAT3-dependent inflammatory feedback loop has been implicated in epigenetic control of transformation. 27 STAT3 has previously been implicated as a prognostic indicator of HCC progression in humans 28 and is currently being tested as a pharmacologic target in HCC therapy. 28,29 This transcription factor also plays a role in cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…27 STAT3 has previously been implicated as a prognostic indicator of HCC progression in humans 28 and is currently being tested as a pharmacologic target in HCC therapy. 28,29 This transcription factor also plays a role in cellular differentiation. Temporarily increased expression of hormone-dependent STAT3 in primed human pluripotent stem cells stimulates cells to undergo an epigenetic shift to na€ ıve-like pluripotency, which suggests a role in increasing the number of stem cell targets for mutational hits and eventual transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Src homology region 2 (SH2) domain-containing phosphatase 1 (SHP-1) belongs to a family of non-receptor PTPs and has been identified as a negative regulator of numerous cytokine signaling pathways [19]. Previous studies have shown that SHP-1 tyrosine phosphatase, which negatively targets phosphorylated (p)-STAT3 signaling in a wide variety of tumors, exhibits significant anti-tumor activity by triggering apoptosis and suppressing tumor formation [20][21][22]. Consequently, the STAT3 pathway may represent a target for therapeutic intervention in CCA.…”
Section: Introductionmentioning
confidence: 99%